Complete mitochondrial genome of the silkworm strain, Chilseongjam Bombyx mori (Lepidoptera: Bombycidae), with a unique larval body marking. Issue 2 (3rd July 2019) - Kim, Seong-Wan; Kim, Min Jee; Kim, Kee-Young; Kim, Seong-Ryul; Kim, Iksoo
Abstract: Recently, a new silkworm strain with a peculiar larval marking and rare cocoon colour was bred in Korea for educational learning and exhibition. In order to obtain the genetic information of the newly bred strain, Chilseongjam Bombyx mori (Lepidoptera: Bombycidae), its complete mitochondrial genome (mitogenome) was sequenced. The mitogenome is 15, 660 bp in length, contains a typical set of genes, and has gene arrangement and composition typical of Lepidoptera. However, the Chilseongjam strain mitogenome is 4–36 bp longer than 19 other strains originating from other countries and 16 bp shorter than the whole genome of a Korean Hukpyobeom strain. In particular, the Chilseongjam strain has an intergenic spacer sequence that is shorter than that of the Hukpyobeom strain at the tRNA His and ND4 junction as it has fewer microsatellite-like AT repeats. Phylogenetic analyses conducted using a total of 21 silkworm strains originating from nine countries revealed a few subgroups with moderate-to-high nodal support (80–94%). The Korean Chilseongjam strain formed a relatively strong subgroup (85%) with a Japanese strain (J106) instead of the Korean Hukpyobeom strain.